The Selective Cytotoxicity of The Hydroalcoholic Extract of Santalum Album Linn Wood on A375 and SK-MEL-3 Human Malignant Melanoma Cells: Cytotoxicity Effect of White Sandal Wood Extract - Bahareh Sadat Yousefsani,; Bita Bahrami,; Ali Qobadi,; Elahe Aghazadeh,; Kobra Shirani,; Jalal Pourahmad, (Iranian Journal of Pharmaceutical Sciences, 2022)
Melanoma is the cause of most skin cancer all around the world because of its high proliferation rate, metastatic nature, and limited effective therapies. According to the rapid increment in its incidence compared to other types of skin cancers, new therapies are seemed to be essential. Natural remedies can be used to treat many diseases, including cancer, so more research is needed. The wood of Santalum album Linn, known as “white sandalwood”, is one of the herbs which is a rich source of antioxidants that can be used as a therapeutic medication in different types of cancers, especially skin cancer. This research aimed to verify the cytotoxic effects of white sandalwood on A375 and SK-MEL-3 melanoma and AGO-1522 normal human fibroblast cell lines. At first, the ethanolic extract was prepared. Then, cell viability and cytotoxic activities were evaluated. Furthermore, ROS formation, lipid peroxidation, and release of cytochrome-c were also assessed. Herb extract significantly increased the death of A375 and SK-MEL-3 melanoma cells (p < 0.001), lipid peroxidation (p < 0.01), and reactive oxygen species (p < 0.01) and cytochrome c concentration (p < 0.001). Meanwhile, the same amount was ineffective and safe on AGO-1522 normal fibroblast cells. The extract of white sandalwood has considerable cytotoxic effects on the human melanoma cell line. Further studies are required to demonstrate the therapeutic effects of white sandalwood on melanoma cancer.